Banking Transactions - Kanda, Hideki (The Sociology of Law, 1995)
The bank-customer relationship in Japan has several distinct characteristics. Some of them are common in other trade relationships in Japan, and others are unique in banking transactions. Banking transactions between banks and their customer firms in Japan show three unique characteristics. First, banks and customer firms engage in a very wide range of transactions, from straightforward lending to new type transactions such as swap transactions and even to bank's stockholding of their customer firms. Second, a firm usually establishes long-term contractual relationships with more than one, and typically several, banks. One of the banks serves as the "main bank". Third, banks obtain a strong legal position under a standard form contract known as the Banking Transactions Agreement, but they sometimes show behavior that looks quite inconsistent with their legal position. These three distinct characteristics are found in many situations including daily credit transactions, rescue actions at the customer firm's financial distress, and bank's stockholding of their customer firm. All of them, however, began to evaporate in recent years. The long-term relationship between banks and their customer firms covering a very wide range of transactions may have produced an exclusivity and thus hindered new entry by competing financial institutions in a particular transaction area. The existence of this exclusivity, however, is debatable, and lacks empirical support.